Water dynamics in confined systems and aqueous mixtures explored by neutron scattering and simulations - Harpham, Michael Robert, author; Levinger, Nancy E., advisor; Ladanyi, Branka, advisor; Barisas, B. G., committee member; Krueger, David A., committee member (Colorado State University. Libraries, 2007)
We investigate binary mixtures of water and DMSO through MD simulations. We evaluate the self-intermediate scattering functions (ISF's), Fs(Q,t), which are related by a Fourier transform to the incoherent structure factors, S(Q,ω), measured in quasielastic neutron scattering (QNS) experiments. We find that translational and rotational motion is slowest at 0.5 mole fraction DMSO. We use our simulation results to also assess the range of validity of the dynamical models used in the analysis of QNS data. We find that the jump-translational diffusion model, used to obtain information about translational diffusion from QNS spectra, represents water translational dynamics quite well. Our MD data suggests that the decoupling approximation, used to extract information on rotational relaxation from QNS spectra, becomes less accurate as the mixture composition approaches XDMSO = 0.5. We find that rotational relaxation deviates quite strongly from the isotropic rotational diffusion model, and we explore this issue further by investigating the behavior of orientational time correlation functions for different unit vectors. We explore the mobility and structure of water molecules in Aerosol OT (bis(2-ethylhexyl) sulfosuccinate, AOT) reverse micelles (RM's) of varying water content and surfactant counterion through simulations and experiments. Experimental QNS results indicate that the water translational and rotational dynamics become more hindered with decreasing water content, and less hindered with increasing counterion size. MD simulations were performed using the Faeder/Ladanyi model (J. Phys. Chem. B, 2000, 104, 1033) of the RM interior to evaluate the ISF's for water hydrogen atoms. Our simulated QNS spectra match experimental data quite well. Our simulations show that the decay of FsCM(Q,t) is nonexponential; we attribute this to confinement effects and decreased water mobility for molecules close to the interface. Rotational relaxation is anisotropic and also exhibits nonexponential decay. Differences in interfacial mobility of water molecules are strongly correlated with structural features, especially ion-water coordination, and the extent of disruption of the water hydrogen bond network by the counterions. Our QNS investigation of surfactant effects on water dynamics within quaternary reverse micelles showed that water motion within these systems is significantly hindered relative to that of bulk water or even water in ternary reverse micelles.
Keywords: chemistry; physical chemistry